African-American Women in Reconstruction in the Shenandoah Valley - Ann Denkler (Nuevo mundo - Mundos Nuevos, 2014)
American History textbooks and public history sites of the eastern United States are replete with fact and fiction about the American Civil War (1861-1865). The Shenandoah Valley region of Virginia, in the northwestern part of the state, for example, saw its share of conflict and the presence of “great” military leaders during the war, and the historic sites in the area focus on these topics. Over the past twenty years or so, this region has even embraced the exhibition and interpretation of African-American history. This paper contributes to the dearth of this African-American scholarship by looking at the history of African-American women in the Reconstruction period in the Shenandoah Valley--women who were free and women who found freedom upon the South’s surrender in the Civil War. What is crucial to this study is how Black women in the Valley, both during and after enslavement, experienced slavery and freedom similarly and differently from other regions in the South. Thus, the dominant paradigms and mythologies of large plantations overseen by single white patriarchs do not adequately describe the entirety of slave history in America and denies African American women the agency they deserve as historical actors. Further, during the Reconstruction period, racist depictions of African American women appeared on written advertisements and postcards, promoting a false and romanticized imagery of Blacks in the South. I will look at some of these images in my paper, but concentrate on the Freedmen’s Bureau records to show the power Black women in the Shenandoah Valley gained, painting a richer picture of their experiences in the Reconstruction Era.